Screening of Sesbania accessions based on early biomass yield (Journal of the Bangladesh Agricultural University, 2017)
Soft, succulent and readily decomposable Sesbania biomass is one of the best sources of organic matter and nitrogen for improvement of poor, nutrient deficit soils. To select high biomass yielding Sesbania accession(s), an experiment was conducted at Field Laboratory of the Department of Crop Botany, Bangladesh Agricultural University, Mymensingh, following a randomized complete block design with three replications. Seeds of 105 accessions from 3 Sesbania species—S. sesban, S. bispinosa and S. cannabina, were sown in the field @ 60 kg/ha on 23 April 2016. The unit plot size was 3 × 2 m2 with a spacing of 50 cm (row-row) × 15 cm (plant-plant). Data on different yield descriptors were recorded at every 10 day intervals up to 60 days after sowing (DAS). Sesbania sesban produced higher biomass yield at the early growth stages (up to 20 DAS), however, S. bispinosa produced higher biomass at the later stages followed by S. cannabina and S. sesban. Therefore, S. sesban can be grown in a very short rotation [Boro rice-(dhaincha)-Jute-T. Aman rice-Mustard and/or Boro rice-(dhaincha)-T. Aus rice-T. Aman rice-Mustard]; and S. bispinosa for a longer period [Boro rice-(dhaincha)-T. Aman rice-Mustard] to maximize organic matter addition to the soil. Ten accessions of S. bispinosa performed better and produced biomass above 30 g/plant (c. 80 t/ha) within 60 DAS. These accessions could be selected for further study for their decomposability, organic matter accumulation, N2-fixing ability and may be processed to release as recommended cultivar(s).J. Bangladesh Agril. Univ. 15(2): 188-192, December 2017